Friction correction of flow stress-strain curve in the upsetting process. (28th January 2021) - Obiko, Japheth
Abstract: This article reports the effects of friction on the flow stress-strain curve obtained from uniaxial compression test. Uniaxial compression test was done at deformation temperature range of 575 °C–650 °C and strain rates of 0.001 s −1, 0.01 s −1, 0.1 s −1 and 0.5 s −1 to a strain of 0.6 using Gleeble ® 3500 thermo-mechanical simulator. The friction parameter was calculated by using the analytical equation from the literature. The study reports the flow stress-strain curve results. The results showed a variation between the measured and the friction corrected flow stress-strain curves. The flow stress variation increased with an increase in strain. This result shows an increase in friction parameter resulting from contact between the die and the workpiece during deformation. The study has shown that the analytical equations used for hot deformation are applicable in analysing warm deformation flow stress-strain curves.